Associate Degrees in Australia : a Work in Progress. - Smith, Helen (Office for Learning and Teaching, 2013)
Final report of a Teaching Fellowship at RMIT University. The aim of this fellowship was to contribute to improved student access to a range of post-school pathways through closer integration between the tertiary sectors with a particular focus on associate degrees. This report introduces a design model that captures the range of aspirations and stakeholder demands that may be encountered and lays out a process for consultation and decision making.